System of activities to favor the motivation towards the practice of chess (Original) (Revista científica Olimpia, 2020)
The present investigation responds to a doctoral training project belonging to the Faculty of Medical Sciences of Bayamo, Granma. It is carried out with the aim of proposing a system of instructive and recreational activities to promote motivation for the practice of chess in students exempted from the Physical Education class for chronic pathologies of the first year of the Medicine career at the Faculty of Medical Sciences of Bayamo. For the materialization of the objective, a population of 50 exempted students from the first year of the Medicine Career is taken, to whom a diagnosis is applied on the problem being investigated, the results confirm that the low level of student participation for the practice of chess it is based on insufficient motivation for said game. Based on these shortcomings, a system of activities, which are submitted to the criteria of specialists to assess their feasibility of application.
Keywords: chess; motivation; exempted; instructive; recreational